Sacred space for the missional church engaging culture through the built environment - McAlpine, William 1922-2004 (Wipf & Stock, 2011)
Sacred space for the missional church examines the strong link between the theology and mission of the Church and the spaces in which and from which that theology and mission are lived out. The author demonstrates that the built environment is not incidental or even subservient to mission. Rather it is a key player in the fulfillment and the communication of that mission. The book begins with a working definition of the missional church, underscoring the connection between God's mission (missio Dei) and the Church's mission. The reader is presented with historical and theological frameworks for sacred space, and reminded of the pivotal role of the built environment in the fulfillment of the mission of the Church. The design and construction of sacred spaces are shown to be fundamentally a theological exercise and not solely a matter of function, pragmatics and fiscal astuteness. The author questions the uncritical application of blanket statements such "form must follow function," and challenges the conviction that it does not matter where worship occurs, only that it occurs. The book addresses genuine concerns such as legitimizing the cost of church buildings and concludes with practical suggestions and essential questions that must be considered in posturing the built environment within the missional praxis of the Church. -- Publisher
Includes bibliographical references (p. 181-198) and index
Is there a place for a place called church? -- The church, the gospel, and culture : defining mission -- A historical framework for sacred space -- A theological framework for sacred space -- The significance of place in fulfilling of the mission of the church -- Missional challenges and opportunities in the twenty-first century -- Where we need to be -- Appendix A: Sacred space walk : a guideline for spiritual reflection
Keywords: Liturgy and architecture; Church architecture; Church buildings; Mission of the church; Heiligtum; Ekklesiologie; Missionstheologie